2011
DOI: 10.12698/cpre.2011.rr69
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment, Retention, and the Minority Teacher Shortage

Abstract: Using nationally representative data, this study empirically grounds the debate over minority teacher shortages by examining trends in recruitment, employment and retention of minority teachers. The study's findings reveal that a gap continues to persist between the percentage of minority students and the percentage of minority teachers in U.S. schools, but contrary to widespread belief this gap is not due to a failure to recruit new minority teachers. The data show that efforts over recent decades to recruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
186
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(190 citation statements)
references
References 51 publications
4
186
0
Order By: Relevance
“…I observed that Black and White teachers had about 3.6 percentage points of average annual retention gap in NC elementary and middle schools from 2004 to 2014. This retention gap is consistent with the national pattern for the years when teacher mobility and attrition data are available from the National Center for Education Statistics (Ingersoll & May, 2011;Marvel et al, 2006). Consistent with prior studies, I found that Black teachers tended to work in hardto-staff schools that serve a larger proportion of students of color or underperforming students, have poorer school supports, and are in lower SES communities.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…I observed that Black and White teachers had about 3.6 percentage points of average annual retention gap in NC elementary and middle schools from 2004 to 2014. This retention gap is consistent with the national pattern for the years when teacher mobility and attrition data are available from the National Center for Education Statistics (Ingersoll & May, 2011;Marvel et al, 2006). Consistent with prior studies, I found that Black teachers tended to work in hardto-staff schools that serve a larger proportion of students of color or underperforming students, have poorer school supports, and are in lower SES communities.…”
Section: Discussionsupporting
confidence: 80%
“…Among all groups, African American males and White females had the highest annual attrition rate. Ingersoll and May (2011) also identified a higher turnover rate for male teachers of color than for other teachers.…”
Section: Literature Reviewmentioning
confidence: 89%
See 2 more Smart Citations
“…1 Furthermore, employers claim that there shortages of qualified workers in STEM areas. 2 National Science Board identifies that the students will be required to develop their STEM capabilities at higher level as compared to the levels in the past, even for low skilled jobs.…”
Section: Introductionmentioning
confidence: 99%